2018
DOI: 10.3389/fcell.2018.00022
|View full text |Cite
|
Sign up to set email alerts
|

Tet Enzymes, Variants, and Differential Effects on Function

Abstract: Discovery of the ten-eleven translocation 1 (TET) methylcytosine dioxygenase family of enzymes, nearly 10 years ago, heralded a major breakthrough in understanding the epigenetic modifications of DNA. Initially described as catalyzing the oxidation of methyl cytosine (5mC) to hydroxymethyl cytosine (5hmC), it is now clear that these enzymes can also catalyze additional reactions leading to active DNA demethylation. The association of TET enzymes, as well as the 5hmC, with active regulatory regions of the genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 56 publications
(100 reference statements)
1
78
0
Order By: Relevance
“…A potential explanation for the unique role of each TET is their ability to bind to different gene sequences, with TET1 directly binding to DNA via its CXXC domain, which is not present in TET2 (Wu and Zhang, 2011;Zhang et al, 2016). Alternatively, TET1 and TET2 could use distinct binding partners and co-factors, which in turn modulate their enzymatic activity (Melamed et al, 2018;Zhang et al, 2017). Together with the lack of compensation, these potential explanations highlight important functional differences between TET1 and TET2 which may deserve future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A potential explanation for the unique role of each TET is their ability to bind to different gene sequences, with TET1 directly binding to DNA via its CXXC domain, which is not present in TET2 (Wu and Zhang, 2011;Zhang et al, 2016). Alternatively, TET1 and TET2 could use distinct binding partners and co-factors, which in turn modulate their enzymatic activity (Melamed et al, 2018;Zhang et al, 2017). Together with the lack of compensation, these potential explanations highlight important functional differences between TET1 and TET2 which may deserve future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Structural studies confirmed that these catalytic domains specifically bind to cytosines in CG dinucleotides in DNA, known as CpG sites and do not bind to other DNA bases and have almost no specificity to the flanking DNA sequences [114]. The three family members of the TET family-TET1, TET2 and TE3-catalyze the successive hydroxylation of DNA methyl cytosine 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC), 5-formylcytosine (5-fC) and 5-carboxycytosine (5-caC) [115]. These 5-mC oxidation products 5-fC-and 5-caC-modified cytosine are the intermediates that are formed during the conversion of 5-mC to unmodified cytosine, impending for the first step for active DNA demethylation pathway [114,115].…”
Section: Ten Eleven Translocation (Tet)-cancer and Effect Of Vitc (Tmentioning
confidence: 99%
“…As described by Jin et al [27] and Melamed et al [28], there are a number of TET enzymes, including at least two isoforms of TET1, one of TET2 and three isoforms of TET3. As reviewed [28], the full-length canonical TET1 isoform appears virtually restricted to early embryos, embryonic stem cells and PGCs. The dominant TET1 isoform in most somatic tissues, at least in the mouse, arises from alternative promoter usage which gives rise to a short transcript and a truncated protein designated TET1s.…”
Section: Tet Enzymesmentioning
confidence: 99%
“…TET2 does not have an affinity for 5-methylcytosine in DNA [31]. The CXXC domain of the full-length TET3, which is the predominant form expressed in neurons, binds most strongly to CpGs modified by 5-carboxycytosine (5caC) (Figure 3), although it does also bind to un-methylated CpGs [28].…”
Section: Tet Enzymesmentioning
confidence: 99%